بناء تغييرالإجتماعي بالرعاية على النهر كدعوة تنمية المجتمع الإسلامي - Niska, Jazilatun; Ansori, Moh.; Halim, Abdul (Proceedings of International Conference on Da'wa and Communication, 2020)
The purpose of this study is to determine the structure of social change in people's lives as the goal of advocating the development of Muslims. The methodology used by researchers in this study is Participatory Action Research which deals with searching, employment, and registration. The research stages with this method are preliminary mapping, acculturation, defining research activities for social change, socialist mapping, forming research groups, formulating questions, designing question-solving strategies, and thinking about community participation. When researchers used the Participatory Rural Appraisal technique. The result of this research is that researchers and the community take care of the river to achieve social change in people's lives. Building community change by organizing the community in caring for rivers is the aim of advocating for the development of the Islamic community. The process of organizing the community in caring for rivers is to improve the quality of rivers and the quality of the environment to educate people about river care. Care for the river is an activity that advocates the development of Muslims to build social change in people's lives. Building community change is an effort to improve the economic, social, and cultural conditions of the community to achieve a better degree of life.